The influence of religion on entrepreneurial behavior: a review on the roles of emotion and religious motivation - Sulaiman, Muna; Hashim, Haslinda; Ali @ Hamid, Mass Hareeza; Ali, Noor Azman (Human Resource Management Academic Research Society, 2019)
Entrepreneurship plays an influential role in economic growth. However, in today’s digitalized world, entrepreneurial journey is perceived as increasingly challenging than before, as the world is becoming increasingly dynamic and full of uncertainties. One of the ways entrepreneurs choose in dealing with this difficulties and challenges in their entrepreneurial journey is to resort to religion. Religion was found to be significantly related to emotion regulations, motivation and behavior. In entrepreneurship field, previous studies on entrepreneurial behavior were mostly focused on personality and psychological traits. Very little attention has been paid to the role of religion in influencing entrepreneurial behavior, particularly on emotion and religious motivation. The objective of this conceptual paper is to discuss the role of emotion and religious motivation in influencing entrepreneurial behavior. The paper provides discussion and suggestions for future studies on entrepreneurial behavior, guidelines for practitioners, learning institutions and policymakers.